Sistem Aplikasi Location Based Service untuk Pengembangan Kota Cerdas - Sukerta, Agus; Linawati, Linawati; Wirastuti, NMAE Dewi (Majalah Ilmiah Teknologi Elektro; Vol 14 No 1 (2015): (January - June) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2015.v14i01p05)
One way to accomplish the smart city is by utilizing application that build interaction between society and the government while providing the benefits to all stakeholders. This application systems should be reached easily and relatively cheap for the society, and they can be used anytime, anywhere. This paper describes how to develop applications that implement the Location Based Services (LBS) for Development of Smart City to build the Public Complaints Service Application System (PCSAS). The PCSAS was designed, built and then tested. This PCSAS was built with Web-based Client-Server architecture. On the client side using a web interface or mobile with Android operating system. This application uses a valid e-mail as a condition of enrollment, while accommodating Social Media interface particularly Facebook and Twitter to get into the system. The result of the use of this application system was an interaction between the community and the government in handling public complaints. Location information problems in the field may soon be known precisely by coordinates, so that the handling can be done quickly and with sufficient preparation equipment based on the information of the real conditions in the field in the form of photos and videos that are included in the complaint.
Keywords: Smart City, LBS, Public Complaints, Web and Mobile Application